Rooster Town: Winnipeg’s Lost Métis Suburb, 1900–1960 - Burley, David (Urban History Review / Revue d'histoire urbaine, 2013)
In the spring of 1959 the City of Winnipeg ordered the removal of fourteen families, mostly Métis, from land needed for the construction of a new high school in south Winnipeg. For at least a decade, the presence of Rooster Town, as the squatters’ shantytown was known, had drawn complaints from residents of the new middle-class suburbs who objected to the proximity of families of mixed ancestry who seemed indolent, immoral, and irresponsible and whose children brought contagious diseases into the elementary school. Suburban anxieties gave expression to a much deeper municipal colonialism that since the incorporation of Winnipeg had denied Aboriginal people a place in the city. Various agencies of municipal governance and the processes of urban development dispossessed indigenous peoples and pushed them farther onto the edges of the city until no space remained for them. The removal of Rooster Town erased the last visible evidence of a continuing Métis community that had survived in the area since the nineteenth century and that at its peak in the 1930s had numbered several hundred residents.